Adherence and resource use among patients treated with biologic drugs: findings from BEETLE study - Degli Esposti L; Sangiorgi D; Perrone V; Radice S; Clementi E; Perone F; Buda S (Dove Medical Press, 2014)
Luca Degli Esposti,1 Diego Sangiorgi,1 Valentina Perrone,2 Sonia Radice,2 Emilio Clementi,3,4 Francesco Perone,4,5 Stefano Buda1 1CliCon Srl Health, Economics and Outcomes Research, Ravenna, Italy; 2Unit of Clinical Pharmacology, Department of Biomedical and Clinical Sciences, L Sacco University Hospital, Università di Milano, Milan, Italy; 3Unit of Clinical Pharmacology, Department of Biomedical and Clinical Sciences, CNR Institute of Neuroscience, L Sacco University Hospital, Università di Milano, Milan, Italy; 4Scientific Institute, IRCCS E Medea, Lecco, Italy; 5Local Health Unit, Caserta, Italy Objectives: Systemic administration of anti-tumor necrosis factor alpha (anti-TNF alpha) leads to an anti-inflammatory and joint protective effect in pathologies such as rheumatoid arthritis, psoriasis, and Crohn's disease. The aim of this study was to assess adherence to therapy, persistence in treatment (no switches or interruptions), and consumption of care resources (drugs, outpatient services, hospitalizations). Methods: We conducted an observational retrospective cohort analysis using the administrative databases of five local health units. Patients filling at least one prescription for anti-TNF alpha between January 1, 2009 and December 31, 2011 were included and followed up for 1 year. Patients were defined as adherent if >80% of the follow-up period was covered by drugs dispensation. Results: A total of 1,219 patients were analyzed (mean age 49.6±14.6, male 47%). Among enrolled patients, 36% were affected by rheumatoid arthritis, and 31% and 10% were affected by psoriasis and Crohn's disease, respectively; other indications remained below these percentages. Thirty-four percent of patients (420) were treated with adalimumab, 51% (615) with etanercept, and 15% (184) with infliximab. Among the 94% of patients who did not switch, those treated with infliximab had a higher rate of adherence across all indications (51% overall) when compared to that observed in patients treated with etanercept (27%) or adalimumab (23%). The mean annual nonpharmacological expenditure for each patient in analysis was €988 for adherent and €1,255 for nonadherent patients. Infliximab was associated with the lowest cost for all indications as determined by the multivariate generalized linear model. Conclusions: Patients treated with infliximab were associated with higher adherence and persistence in treatment and lower costs, as compared to those treated with adalimumab or etanercept. Keywords: anti-TNF alpha, therapy adherence, cost of illness